MOTIVASI WANITA BEKERJA DAN PENGARUHNYA TERHADAP KONTRIBUSI PENDAPATAN WANITA DALAM MEMBANTU PENDAPATANKELUARGA DI KECAMATANMARPOYAN DAMAIKOTA PEKANBARU - Yessi Nesneri dan Virna Museliza (Marwah: Jurnal Perempuan, Agama dan Jender, 2014)
Currently women, not only serves as a housewife who serves her husband, children, and all members of her family, but many women have other jobs besides housework. Some women no longer be the primary educators for children the next generation, because they have to do quite time consuming job outside the home. As a result, many emerging daycare to address the problem of child care that his/her mother worked. This was triggered by the emancipation of women and the social and economic demands of the household is quite heavy encourage women to earn a living to supplement the family income in order to achieve the welfare of the family. This study aims to determine the factors that motivate women to work and to find out how much revenue contribution of women to the family income. To achieve these objectives, the research done by using three (3) independent variables, namely Women’s income (X1), Working Time Allocation (X2), and Total Dependent in the Family (X3). Analysis of the data used in this research is descriptive and quantitative analysis, using the tool SPSS windows version 22, with multiple linear regression analysis, F test (Test Simultaneous), t test (Partial Test), and the Determination Test (R2). The result shows that the two independent variables (Women’s Income, and Total Dependents in the familyhave significant effect on the dependent variable (Contributions of Women in Family Income (Y)). While the Working Time Allocation variable does not have significant influenceto Contributions of Women in Family Income (Y). in addition, there is a contribution of independent variables (independent) on the dependent variable (dependent) amounted to 60.3%, while the remaining 39.7% is influenced by other variables not examined in this study